A review of growth and development of oncology nursing in six European countries - Charalambous, Andreas; Dielenseger, Pascale; Tsitsi, Theologia; Foulkes, Mark; Dodlek, Nikolina; Fernández-Ortega, Paz; Grov, Ellen Karine; Utne, Inger (My University, 2023)
Oncology nursing consists of a branch of nursing specialised in the care of people affected by cancer. Despite its essential contribution in the field of oncology, there is lack or poor recognition as a specialty across Europe. The aim of this paper is to review the development and growth of oncology nursing in 6 diverse countries in Europe. The paper has been developed by drawing on the relevant national and European literature (e.g., in local language and English language) available in the participating countries. European and international literature has been used complementarily to contextualised the findings to the wider field of cancer nursing across the world. Furthermore, this literature has been utilised to demonstrate how the implications of the paper's outcomes can be relevant to other cancer nursing contexts. The paper discusses the pathways of the development and growth of oncology nursing in France, Cyprus, UK, Croatia, Norway, and Spain. This paper will further contribute to raising the awareness on the extent and level of contribution that oncology nurses are making to improve cancer care on a global scale. This also needs to be in accordance to the policy frameworks on a national, European and global context so that the recognition of the vital contribution of oncology nurses is complemented with its full recognition as a distinct specialty.
Keywords: Oncology; nursing growth; nursing; education; curriculum